2021
DOI: 10.1016/j.sjbs.2021.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of Gastrocotyle hispida (Forssk.) bunge and Heliotropium crispum Desf. and evaluation of their multiple in vitro biological potentials

Abstract: Medicinal plants largely serve as a source of bioactive compounds in traditional medicines to cure various diseases. The present study was aimed at chemical composition, antioxidant, antimicrobial, cytotoxic and antihemolytic potential of five different extracts of G. hispida and H. crispum (Boraginaceae). G. hispida methanolic extract displayed highest number (eleven) of polyphenolic compounds by using high performance liquid chromatography (HPLC). Functional grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The main mechanism used for phytofabrication of NPs is due to the presence of phytochemicals (Iqbal, Abbasi, Ahmad, Batool, et al, 2018; Iqbal, Abbasi, Khalil, et al, 2018; Iqbal, Abbasi, Ahmad, Batool, et al, 2019; Iqbal, Abbasi, Mahmood, Hameed, et al, 2019; Iqbal, Abbasi, Mahmood, et al, 2019; Shahbaz et al, 2021; Ali, Khan, Batool, Shah, et al, 2021; Ali, Khan, Iqbal, Shah, et al, 2021). The major phytochemical responsible for the reduction, stabilization and capping of NPs are carboxylic acids, aldehydes, ketones, amides, quinones, flavonoids, terpenoids, polysaccharides, and proteins (Iqbal, Abbasi, Ahmad, Mahmood, Kanwal, et al, 2018; Iqbal, Abbasi, Ahmad, Mahmood, Ali, et al, 2018; Abbasi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism used for phytofabrication of NPs is due to the presence of phytochemicals (Iqbal, Abbasi, Ahmad, Batool, et al, 2018; Iqbal, Abbasi, Khalil, et al, 2018; Iqbal, Abbasi, Ahmad, Batool, et al, 2019; Iqbal, Abbasi, Mahmood, Hameed, et al, 2019; Iqbal, Abbasi, Mahmood, et al, 2019; Shahbaz et al, 2021; Ali, Khan, Batool, Shah, et al, 2021; Ali, Khan, Iqbal, Shah, et al, 2021). The major phytochemical responsible for the reduction, stabilization and capping of NPs are carboxylic acids, aldehydes, ketones, amides, quinones, flavonoids, terpenoids, polysaccharides, and proteins (Iqbal, Abbasi, Ahmad, Mahmood, Kanwal, et al, 2018; Iqbal, Abbasi, Ahmad, Mahmood, Ali, et al, 2018; Abbasi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 246 , 247 , 248 Ethno‐medico‐botanicals have been used across almost all the cultures worldwide against an array of human medical conditions. 50 , 51 , 52 , 53 The use of betel leaf alone and with a combination of other plants or medicines for better therapeutic effects is mentioned in the Ayurvedic literature, which was almost 1400 BC ago. 54 Atharved, the ancient Vedic literature, mentioned the usefulness of the betel plant against numerous diseases at about 3000–2500 BC before.…”
Section: Traditional and Ethno‐medicinal Usementioning
confidence: 99%
“…Traditional medicine has played a crucial role in the health care of the rural and urban people 246‐248 . Ethno‐medico‐botanicals have been used across almost all the cultures worldwide against an array of human medical conditions 50‐53 . The use of betel leaf alone and with a combination of other plants or medicines for better therapeutic effects is mentioned in the Ayurvedic literature, which was almost 1400 BC ago.…”
Section: Traditional and Ethno‐medicinal Usementioning
confidence: 99%
“…According to the World Health Organization, 80% of world depends on the traditional use of plants to cure diseases and this dependency is increasing day by day because of cost-effectiveness, safety, and high quality as compared to synthetic marketed drugs [ 13 ]. Research studies have revealed that different medicinal plants and their constituents possess antiproliferative [ 9 ], antimicrobial [ 14 ], antioxidant, antihemolytic [ 15 ], anticancer [ 11 , 16 ], antidepressant [ 17 , 18 ], antioxidant, anti-inflammatory, analgesic, antinociceptive [ 19 ], antiarthritic, aphrodisiac, analgesic [ 12 , 20 ], and other pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%